1999
DOI: 10.1007/bf02881753
|View full text |Cite
|
Sign up to set email alerts
|

Transfer ofE. coli gutD gene into maize and regeneration of salt-tolerant transgenic plants

Abstract: GutD gene, encoding a key enzyme (glucitol-6-phosphate dehydrogenase) of sugar alcohol metabolic pathway inE. coli, was transferred into maize. Results of Southern and Western blotting analysis certified that this gene had integrated and been expressed in transgenic maize plants and their progeny. The synthesis and accumulation of sorbitol were detected in transgenic maize plants and a preliminary nutrient solution culture experiment showed that gutD transgenic maize plants had an increased tolerance to salt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Plant salinity resistance genes that present greater levels of tolerance towards salt stress, have been identified, isolated and transferred (for more detailed information see Kolodyazhnaya, 2009). To increase salt tolerance, the gutD gene of Escherichia coli was used to confer salt resistance in corn plants (Liu et al, 1999). It has also been demonstrated that transgenic tomato plants accumulating polyamines are capable to tolerate high temperature stress (Cheng et al, 2009).…”
Section: Biotic and Abiotic Stress Resistancementioning
confidence: 99%
“…Plant salinity resistance genes that present greater levels of tolerance towards salt stress, have been identified, isolated and transferred (for more detailed information see Kolodyazhnaya, 2009). To increase salt tolerance, the gutD gene of Escherichia coli was used to confer salt resistance in corn plants (Liu et al, 1999). It has also been demonstrated that transgenic tomato plants accumulating polyamines are capable to tolerate high temperature stress (Cheng et al, 2009).…”
Section: Biotic and Abiotic Stress Resistancementioning
confidence: 99%
“…Crops with resistance to viruses, pathogenic bacteria and fungi, and nematode and insect pests are nearing release (for example, Murray et al, 2002;Sharp et al, 2002). Newer technologies include: improved crop resistance to limiting environmental factors such as drought, salinity and toxic metals (de la FuenteMartinez et al, 1997;Liu et al, 1999;Garg et al, 2002;Song et al, 2003); enhanced nutrient content (Goto et al, 1999;Lucca, 1999;Bovy et al, 2002), including nutriceuticals; pharmaceutical or 'pharm' crops (Thanavala et al, 1995;Stoger, 2000); crops that bioaccumulate toxins for use in soil remediation (Song et al, 2003); and crops that produce industrially useful products, such as starches and plastics.…”
Section: Pipeline Technologiesmentioning
confidence: 97%
“…Using these technologies, drought-resistant soybean varieties (De Ronde et al, 2001) have been created, as has rice that is both drought and salt tolerant (Garg et al, 2002). Salt-tolerant maize, tomatoes, oilseed rape, and tobacco have been engineered by Liu et al (1999), , and Singla-Pareek et al (2003), respectively. Plants genetically manipulated to withstand the high levels of aluminium typical of increasing soil acidity due to improper land management have also been created (de la Fuente-Martinez et al, 1997;de la Fuente-Martinez and Herrera-Estrella, 1999).…”
Section: Potential Benefits Of Transgenic Cropsmentioning
confidence: 99%
“…A recently discovered halophytic plant species, Thellungiella halophila (also known as T. salsuginea), has emerged as a new model plant for the molecular elucidation of abiotic stress tolerance [77]. The gutD gene from Escherichia coli can also be used to provide salt tolerance [79]. A salt tolerance gene isolated from mangrove (Avicennia marina) has been cloned, and can be transferred to other crop plants [78].…”
Section: Salt Tolerancementioning
confidence: 99%